Implementación de contabilidad comercial en la empresa “Ferretería El Constructor” en la ciudad de Loja, período: mayo a junio del 2016 - Maura Ochoa, Nasly Carolina (2017)
The development of this thesis entitled "COMMERCIAL IMPLEMENTATION OF ACCOUNTING IN THE COMPANY FERRETERIA BUILDER" IN THE CITY OF LOJA, PERIOD: MAY TO JUNE 0 6 "allowed to implement the knowledge acquired during the years of study in the career of Accounting and Auditing in the form of distance learning UED fulfilling the need for the degree of Engineer in Accounting and Auditing, Certified Public Accountant Auditor, basing its structure in the regulations Academic Regime current requirement at the National University of Loja. The proposed objectives were met in full especially with the introduction of commercial accounting important considering its use will help keep a daily record of all business operations of the company, by organizing documents, preparation of the Initial Inventory based on physical verification of the goods of assets, liabilities and equity himself; Plan and Manual accounts according to the needs of the company was designed; finally the design of the auxiliary registers, allowed to follow a systematic order of operations in the general journal, achieving run the accounting process from the baseline to the financial statements. At the end of the investigation was obtained as conclusion the development of real and timely financial statements therefore the owner is recommended to continue applying the accounting process for better control of daily transactions in such a way that reflect reliable results that help in decision making for better positioning the company in the commercial field.